Perceptions of Papuan Students and Students regarding the Issue of the Expansion of Papua - Melyana R. Pugu; Helmawaty E. Rumbiak; Endrina R. Priyanka (Budapest International Research and Critics University, 2022)
This study aims to obtain a clear analysis of the driving and inhibiting factors for the formation of regional expansion in Papua Province according to the views and perceptions of Papuan students who are scattered at home and abroad. The method used in this study is a qualitative research method, namely research data that focuses on events in society by collecting data both primary and secondary which are then triangulated and obtain valid data to then be used to answer the problems raised. The output of this research is that Papuan students as the nation's young elite consider it important to make an in-depth study of the readiness of the indigenous Papuans when the territory is divided so that the indigenous Papuan community does not become a spectator in the development and the objectives of Papua's special autonomy are achieved with indicators of increasing the welfare of the indigenous Papuans.